Psycholinguistic bases of speech adaptation by immigrant children - Tarasiuk, Inna (Lesya Ukrainka Eastern European National University, 2014)
The article focuses on the issue of speech adaptation of immigrant children to a foreign environment. Speech adaptation is defined through the main psycholinguistic features and functions of both constituents – adaptation and speech. The concept is viewed as the effective use of all language means available in linguocultural environment for realizing individual needs, motives and obtaining new values. It was found out that in the course of speech adaptation, immigrants were strengthening their cognitive abilities, were developing volition, while manifesting personal growth and self-realization. Because of its individual nature, speech adaptation is not limited by age, temporal features, and area of inhabitancy. The empirical study results clearly show the influence of gender, school type, and psycho-emotional states of immigrant children on their successful speech adaptation. Furthermore, a psycho-didactic training program aimed at developing speech adaptation by immigrant children was designed. The results of a psycholinguistic experiment held with control and experimental groups show the efficacy of the introduced psycho-didactic training program that facilitates immigrant childrens’ speech adaptation.
Keywords: speech adaptation; immigrant children; foreign environment; psycho-didactic training program